THEORETICAL FOUNDATIONS OF PROCESS MANAGEMENT IN THE CONDITIONS OF CHANGE - Verbovska, L. S.; Fastivskyy, G. V.; Yatsko, V.M. (The actual problems of regional economy development, 2024)
The article examines the theoretical foundations of process management in conditions of change and the importance of knowledge in process management for a business entity. The relevance of this study is an important component of the modern approach to the process of managing changes, knowledge and business processes, forming not just an understanding of all processes in the management structure, but also the use of the Deming cycle as a procedure for implementing a management system and managing processes in the organization. The importance of using a process approach is determined, because it will allow to evaluate, monitor business processes, make changes through optimization or reengineering, manage knowledge and changes in the organization, the compliance of the management accounting system in business processes will reduce the costs of developing an information base, integration of various information systems and their support. It has been proven that an important aspect of change is Lippitt's theory of change, which includes awareness of the need for change; development of the relationship between the system and the change agent; identification of change problems; establishment of change goals, action plan for their achievement; implementation of changes; staff perceives changes as such; stabilization; redefining the change agent's relationship with the system. The obtained theoretical studies showed that, in terms of methodological development research, the application of the tool presented by us in business processes is an important component in the process of implementing change and knowledge management for a business entity. At the same time, it is determined that business processes and formalization, knowledge in the conditions of changes, effective management of them, is the basic technology of modern management, and the described business processes serve as a road map for interested parties, owners of the organization and business process for the implementation of process redesign in if necessary, or at different stages is quite useful for both stakeholders and the organization itself. Therefore, the management of changes and knowledge plays an important role in business processes and their management, and the chosen topic of the article is relevant in scientific and applied aspects.